Keterampilan sosial pustakawan dalam memberikan layanan prima kepada pemustaka di era Information, Communication and Technology (ICT) - Wahyuni, Sri (Daluang: Journal of Library and Information Science, 2023)
Purpose. The aim of this research is to provide knowledge to librarians that the importance of social skills is seen from attitudes and behavior in providing excellent service. Library services are an important indicator in determining user satisfaction. So librarians need to focus on user-oriented services.Methodology. The type of research used in this paper is library research. Data collection was obtained through reference books, scientific journals, relevant research related to research and other sources of information that support this research. The literature data taken comes from 2017-2022. The data analysis technique begins with the researcher obtaining library sources which the researcher collects first from various sources, then arranges them and classifies them, then analyzes them, classifies them and interprets them to obtain conclusions.Results and discussion. The results showed that the social skills that librarians should have in providing primary services to users using the principles of people-based service and service excellence are aimed at satisfying their libraries, increasing loyalty, and increasing the number of libraries visiting the library. Moreover, in terms of service, at least a librarian must have competence in the current era of information and information technology. The four categories that he must have are knowledge, skill, affective, and pragmatic model approaches. These four things are the basis for the librarian's activity, especially the section of service.Conclusions. The role of librarians in the era of information, communication, and technology (ICT) must be an agent of change for society.  It aims to provide excellent service to users, thereby improving the quality of libraries in the eyes of the public with the hope that the library becoming the center of community activity in study life.